PREFERENCE FOR DRY FISH AMONG ADOLESCENT GIRLS - Leela, M. Sai; Sony, V.; Singh, Dipali Kumari (International Journal of Research -GRANTHAALAYAH, 2021)
Dry fish consumption is traditionally part of the diets in Andhra Pradesh. The present study aims at understanding the current trend in dry fish consumption in the context of urbanization. The study comprised of 490 college going adolescent girls (non-vegetarians) from Andhra Pradesh, India. The dietary data was elicited by the Food frequency method. The study points that dry fish is preferred by adolescents in both urban and rural areas of Andhra Pradesh.